Difference in jumping ability and body composition in competitive volleyball setters - Vuleta, D.; Jerak, T.; Sporis, G. (Acta Kinesiologica, 2016)
The purpose of this study was to determine the difference in physical performance and body composition in competitive volleyball setters. Ninety volleyball players participated in this study. Players were members of Volleyball clubs in three different levels. Players performed assessments of body composition and vertical jump. Significant differences were found in all variables except for BMI which had no significant differences at the 0.05 level. This study has confirmed that jumping ability could discriminate players in different level of play in volleyball.